2016
DOI: 10.1002/hast.588
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Cognition and Gifts: How Does social Psychology help Us Think Differently about Medical Practice?

Abstract: This article takes the following two assumptions for granted: first, that gifts influence physicians and, second, that the influences gifts have on physicians may be harmful for patients. These assumptions are common in the applied ethics literature, and they prompt an obvious practical question, namely, what is the best way to mitigate the negative effects? We examine the negative effects of gift giving in depth, considering how the influence occurs, and we assert that the ethical debate surrounding gift-givi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The susceptibility of health care professionals to these influences can then be heightened by motivated reasoning and illusory superiority-the impulse to believe that physicians are as impartial as they would like to be and that society expects them to be. 45 This was shown in one study of 467 resident physicians wherein 61% believed they were unbiased by interactions with pharmaceutical companies but believed that the same was true for only 16% of their peers. 47 These forces work at an unconscious level, demonstrated in a study that found physicians' prescribing behavior changed in the months following industry-sponsored grand rounds, despite no longer remembering the sponsor, 48 and another that found that prescribing behaviors changed after physicians attended an industry-sponsored continuing medical education event, despite being queried beforehand whether they believed the event would change their behavior.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The susceptibility of health care professionals to these influences can then be heightened by motivated reasoning and illusory superiority-the impulse to believe that physicians are as impartial as they would like to be and that society expects them to be. 45 This was shown in one study of 467 resident physicians wherein 61% believed they were unbiased by interactions with pharmaceutical companies but believed that the same was true for only 16% of their peers. 47 These forces work at an unconscious level, demonstrated in a study that found physicians' prescribing behavior changed in the months following industry-sponsored grand rounds, despite no longer remembering the sponsor, 48 and another that found that prescribing behaviors changed after physicians attended an industry-sponsored continuing medical education event, despite being queried beforehand whether they believed the event would change their behavior.…”
Section: Discussionmentioning
confidence: 99%
“…These are the exposure effect, which creates a preference for something seen before; the frequency effect, which creates greater willingness to accept an idea (like 1 drug is superior to another) if repeatedly exposed to the idea; and implicit social pressure toward reciprocity. 45,46 Reciprocity can certainly encompass the sense of collegiality that may emerge after repeated interactions and meals with sales representatives but can also be triggered by gifts and gestures between relative strangers. The susceptibility of health care professionals to these influences can then be heightened by motivated reasoning and illusory superiority-the impulse to believe that physicians are as impartial as they would like to be and that society expects them to be.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations